1999
DOI: 10.1086/302599
|View full text |Cite
|
Sign up to set email alerts
|

STAT5 Signaling in Sexually Dimorphic Gene Expression and Growth Patterns

Abstract: The past 10 years have seen enormous advances in our understanding of how cytokine signals are mediated intracellularly. Of particular significance was the discovery of a family of seven Signal Transducer and Activators of Transcription (STAT) proteins. Each of these has now been studied in detail, and appropriate gene-disrupted mouse models are available for all except STAT2 (Leonard and O'Shea 1998). Fetal lethality is observed in Stat3-deficient mice, and various immunodeficiencies characterize mice with di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
0
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(55 citation statements)
references
References 36 publications
(48 reference statements)
5
48
0
2
Order By: Relevance
“…Thus, STAT5B is unique among the GHactivated STATs in that it is appropriately sensitive to pulsatile GH, suggestive that many of the physiological actions of GH in males may be mediated in part by STAT5B. Studies of gene expression and body growth using STAT5B-de®cient mice have supported this view (Davey et al, 1999c;Teglund et al, 1998;Udy et al, 1997).…”
Section: Stat5b Is Responsive To Pulsatile Ghmentioning
confidence: 96%
“…Thus, STAT5B is unique among the GHactivated STATs in that it is appropriately sensitive to pulsatile GH, suggestive that many of the physiological actions of GH in males may be mediated in part by STAT5B. Studies of gene expression and body growth using STAT5B-de®cient mice have supported this view (Davey et al, 1999c;Teglund et al, 1998;Udy et al, 1997).…”
Section: Stat5b Is Responsive To Pulsatile Ghmentioning
confidence: 96%
“…4 Targeted deletion of STAT5b alone results in growth failure due to impaired growth hormone (GH) signaling, without spontaneous autoimmune disease. [5][6][7][8] A nonredundant role for STAT5b in preventing mucosal inflammation has not previously been proposed. Although our group and others have shown that GH administration will improve symptoms in patients with CD and reduce mucosal inflammation in several animal models of colitis, whether this involves mucosal STAT5b activation is not known.…”
mentioning
confidence: 99%
“…Por el contrario, la STAT5b es la principal forma de STAT5 en el hígado (1 l ) , donde se activa en respuesta al estímulo por el patrón intermitente de secreción de GH, característico de las ratas macho adultas, pero no por el patrón de secreción casi continuo característico de las ratas hembra adultas (14). Los modelos de mutación específica de cada uno de los genes de STAT5, han permitido establecer que la STAT5b se requiere para mantener el dimorfismo sexual en las respuesta a la GH (8) y concluir que las isoformas STAT5a y STAT5b se requieren, individual o conjuntamente, en casi todas las respuestas biológicas asociadas con la GH (15,16).…”
Section: Discussionunclassified